FAKTOR-FAKTOR YANG MEMPENGARUHI ALIH FUNGSI LAHAN PERTANIAN DI KABUPATEN MINAHASA SELATAN - Vinny I. Lagarense; Gene H.M. Kapantow; Ribka M. Kumaat; Lorraine W. Th. Sondak (Universitas Sam Ratulangi, 2015)
ABSTRAKThis study aimed to analyze the factors that affect the conversion of agriculturalland to non-agricultural in South Minahasa Regency. In particular, this study analyzed the effectof population, GRDP per capita, and number of industry to the change of the area of agriculturalland.This study was conducted using secondary data obtained from the office of BPS (CentralBureau of Statistics) South Minahasa. The data was then analyzed using multiple linearregression analysis.The results showed that only GRDP per capita which significantly affectedthe areaagricultural land in South Minahasa Regency. If GRDP per capita increased, the area ofagricultural land would decrease. This was an indication that when the people income increased,the land requirement for non-agricultural activities such as housing, offices, and otherinfrastructure would also increase. The required land tended to be converted from agriculturalland.